PENGARUH INFORMASI LABA DAN ARUS KAS TERHADAP HARGA SAHAM - Mutia, Evi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
The objective of this research is to examine and find out empirical evidence of the influence ofinformation of earnings and cash flow on stock price. This study uses LQ 45 companies listedon Indonesian Stock Exchange as the study population. The data used is secondary data inthe form annual reports, financial statements, balance sheets, and notes to financialstatements on LQ 45 companies for period Agustus 2008 - February 2009. Taking target 45firms by using purposive sampling method and cross-section multiple regression model asanalyzing tool, the result of this research show that information of earnings, investingactivities of cash flow and Financing activities of cash flow have a significant effect to stockprice of LQ 45 companies which are listed on Indonesian Stock Exchange, but operatingectivities of cash flow and sum of cash flow have no significant effect to stock price of LQ 45companies which are listed on Indonesian Stock Exchange.Keywords: Earning, cash flow and stock price